A study construction waste management in construction site at Kota Bharu Kelantan / Nor Asmaniza Md Asam - Md Asam, Nor Asmaniza (2021)
It is certain that there will always be trash on the building site in a normal construction project. Construction waste encompasses undesirable materials created by the construction industry, either directly or by accident. Materials such as bricks, cement, sand and wood were damaged during construction or left unusable for different reasons. For example, piles, nails and insulation are included in the construction waste. Also included are wires and roof tiles as well as concrete, steel bars, formwork and other waste generated by site cleaning, such as tree stumps, hedgerows, rubble and tree stumps, which are included in the construction waste category. When it comes to effective waste management, the construction sector is lagging behind other industries. If the contractor wants to find a method to use the materials instead of disposing of them, they can still do so. As a result, this page provides some recommendations on how to manage these materials as reusable trash. Next, a number of factors are conducive to good waste management in the workplace. Finally, the construction sector is encouraged to improve its waste management practises. Construction sites are notoriously unpredictable, therefore there are a number of ways to reduce waste on construction sites. A modest rise in trash output and associated difficulties with waste disposal are plaguing Malaysia. The aim of this research is mainly focus on aim of this research is mainly focus on study the construction waste management in construction site which lead to a sustainable site to identification the types of construction waste in construction site and to determine method of construction waste management used towards sustainable construction site. This research will involve in setting and distributing a set of questionnaires to project manager, site manager, site clerk, site workers and others to gets more information about method used in waste management construction.